Subtitusi Tepung Komposit (Ketan Hitam-Kacang Hijau dan Terigu) Terhadap Karakteristik Sensori dan Kesukaan Thin Brownies - Putra, Dafa Lakundha Cahyadi; Any Sutiadiningsih; Lilis Sulandari; Ila Huda Puspita Dewi (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2025)
Thin Brownies is one of the innovations of brownie products. Thin Brownies is better known as brownie chips or brownchips. The method used is to conduct experiments substituting 30%, 40%, and 50% wheat flour with composite flour (black sticky rice-mung beans) with a ratio of 70%:30%. This sensory test was carried out by trained and semi-trained panelists, assisted by distributing observation sheets with an assessment (5-1) and nutritional tests were carried out in the laboratory. Data analysis used the One Way method, the best data analysis results were found in product 120 with 40% wheat flour substitution, composite flour (black sticky rice-mung beans) with a ratio of 70%:30%. and assisted by sensory characteristics based on color, texture, aroma, taste, color preference, taste preference, texture preference, aroma preference. The best product has a nutritional content of 77.94% carbohydrates, 9.68% protein, 8.11% fat, 3.01% fiber and 1.24% water content.